2022
DOI: 10.2991/absr.k.220207.027
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Helminth Infections on Smallholder Farming Beef Cattle at Palm-Cow Integration in East Kalimantan and Riau provinces, Indonesia

Abstract: An integrated palm-cow management system has been introduced to increase population and production of beef cattle in Indonesia. The objective of the study was to assess the helminth infections on beef cattle in the palm-cow integration in East Kalimantan and Riau provinces under smallholder farming system. A cross sectional survey was carried out during November -December 2020 to observe diseases occurrence, interview the owner and animal health officer, as well as collected faecal sample of cattle in extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The prevalence of fasciolosis was 16.50% in dairy cattle in Boyolali, Central Java, Indonesia [21]. A high prevalence of fasciolosis was reported from a smallholder beef cattle farm from a palm-cow integration system in East Kalimantan, in Bali cattle, raised extensively (65.5%) and Brahman cross cattle raised intensively (32%) [22]. These results indicate that location and management system are likely the primary determining factors for the prevalence and frequency of fasciolosis.…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of fasciolosis was 16.50% in dairy cattle in Boyolali, Central Java, Indonesia [21]. A high prevalence of fasciolosis was reported from a smallholder beef cattle farm from a palm-cow integration system in East Kalimantan, in Bali cattle, raised extensively (65.5%) and Brahman cross cattle raised intensively (32%) [22]. These results indicate that location and management system are likely the primary determining factors for the prevalence and frequency of fasciolosis.…”
Section: Discussionmentioning
confidence: 85%
“…The most prevalent illness was caused by strongyle-type parasites. Fasciola gigantica is a type of trematode that is often found in the liver, Martindah [8] reported that the incidence in East Kalimantan reached 50% and Paramphistomum reached 63% while in Riau province it was smaller at 23.91% for Fasciola and 15.22% for Paramphistomum. The incidence of fasciolosis is influenced by two main factors, namely temperature and environmental humidity, which accelerate the hatching of Fasciola eggs and the snail population in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…According to other reports, 87 out of 109 samples in Banten province tested positive for gastrointestinal parasites [7]. The prevalence rates of nematodes in East Kalimantan and Riau provinces were recorded as 18.5% and 32.61%, respectively [8]. Several variables, including humidity and temperature, can impact the rate at which nematode infections spread in Indonesia, a tropical nation.…”
Section: Introductionmentioning
confidence: 97%